ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERLANJUTAN UMKM DI ERA PANDEMI COVID-19 (STUDI KASUS KABUPATEN SIDOARJO) - Basuki, Alif fikri; Dias satria (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
MSMEs are one of Indonesia’s national main economic pillars, with the contribution of those in Sidoarjo alone in 2019 of IDR 1.6 trillion. However, their business had to be disrupted by the rocketing cases of Corona Virus Disease (Covid) not long after. They had to struggle with sales decrease, raw material scarcity, distribution clogging, capital deficiency, and production reduction due to labor layoffs. This research aims to identify factors that influence the sustainability of MSMEs in Sidoarjo and measures required by them in order to maintain their sustainability during the pandemic. The scope of this study is the effects of business owner’s resources, environmental carrying capacity, financial management, and communication and information technology usage on the sustainability of MSMEs in Sidoarjo Regency. This research applies multivariate regression analysis and SmartPLS 4 as the statistical tools. The results of the analysis indicate that communication and information technology usage and environmental carrying capacity have significant effects on the sustainability of MSMEs in Sidoarjo during the Covid-19 pandemic, but business owner’s resources and financial management have no significant influence. Therefore, it can be concluded that capital aids, tax incentives, internal support from family, access to information technology, and digital marketing can support the sustainability of MSMEs in Sidoarjo during the Covid-19 pandemic.